Electrochemical behavior of Ti-Mo alloys applied as biomaterial - Oliveira, N. T. C. [UNESP]; Guastaldi, Antonio Carlos [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
Electrochemical investigation on the as-cast Ti-Mo alloys (4-20 Mo wt.%) applied as biomaterials in Na2SO4 and Ringer physiological solutions is reported. Analyses of the open-circuit potential indicated that all alloys present spontaneous passivation. SEM and cyclic voltammograms obtained in the Ringer solution showed that the samples studied do not present pitting corrosion at potentials up to 8 V (SCE), indicating high corrosion resistance. Open-circuit potential profiles of the anodic oxides growth in both solutions show that the presence of chloride ions during the anodization does not influence the oxides' chemical stability, and also clearly indicate that adding Mo to pure Ti improves the stability of the anodic oxides. All these results suggest Ti-Mo alloys promissory to be applied as biomaterials. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: titanium alloys; cyclic voltammetry; passivation; anodic films; pitting corrosion